A cross-sectional study on the prevalence of different types of anemias in pregnant women in a rural tertiary care center. - Peethambaram, Ms. Harika; Mokhasunavisu, Dr. Hiranmaye; Tammireddi, Dr Ramya Sindhura; Kollapu, Dr.Anusha; Rani, L. Jhansi; Bhagyalakshmi , Dr. Atla (Student's Journal of Health Research Africa, 2025)
Background: Anemia during pregnancy is a major public health concern, especially in rural areas of developing countries, and is associated with adverse maternal and fetal outcomes. Iron deficiency anemia (IDA) is the most common type, though folate and vitamin B12 deficiencies also contribute. This study assessed the prevalence and distribution of different anemia types among pregnant women in a rural tertiary care setting. Materials and Methods: A cross-sectional study was conducted over 12 months (June 2024–May 2025) at the Department of Pathology and Department of Obstetrics and Gynecology, NRI Institute of Medical Sciences, Visakhapatnam. A total of 150 pregnant women aged 18–40 years with anemia were included. Data were collected from complete blood picture profiles, hemoglobin levels, and nutritional markers, including serum iron, ferritin, folate, and vitamin B12. Statistical analysis was performed using SPSS. Results: Most participants were aged 21–25 years (46%), followed by 26–30 years (24%), 18–20 years (20%), and 31–35 years (9.3%). Iron deficiency anemia was the predominant type (85.23%), followed by vitamin B12 deficiency (10.72%) and folate deficiency (4.69%). Severe anemia (Hb <7 g/dL) was exclusively due to IDA, while B12 and folate deficiencies were more frequent in mild anemia cases. Hematological and biochemical findings were consistent with these nutritional deficiencies. Higher prevalence was observed in women with greater parity and lower socioeconomic status. Conclusion: Iron deficiency overwhelmingly dominates anemia among pregnant women in rural India, with vitamin B12 and folate deficiencies contributing mainly to mild cases, particularly in multiparous women and those of lower socioeconomic status. Recommendations: Strengthened antenatal screening, nutritional counseling, and timely supplementation with iron, vitamin B12, and folate are essential to reduce maternal anemia and improve pregnancy outcomes.